Podstawowe założenia przebudowy prawa pracy - Salwa, Zbigniew (Wydział Prawa i Administracji UAM, 1988)
The article discusses theoretical problems of the Polish labour law reconstruction, focusing its attention on basic directions of the labour law reform. The author begins has considerations with the presentation of the most vital reasons indicating the need to carry out a far-reaching reform of the labour law. Its main purpose should be to synchronize legal solutions with actual socio-economic changes and to ground legal construction on economic mechanisms to a greater degree than in the past. The above refers to provisions realizing both an organizational as well as a protective function of the labour law. Being of the opinion that the Labour Code should remain a basic source of the labour law, the author postulates that the regulations contained in that Code be based mostly on semi-imperative norms allowing, within uniform constructions, to depart from the Code's provisions in legal acts of a lower rank and in a contract for employment in the direction favourable to an employee. The above would make it possible to secure uniformity and coherency of the labour law system and to develop and differentiate the work and pay conditions and other rights of employees in a decentralized manner, mostly by way of normative agreements. It is the author's opinion that the reconstruction of the labour law should increase the importance of a contract for employment, should reduce nomination as a basis of entering into the employment relationship and should lead to the elimination of appointment as a separate, known only in the Polish labour law, source of the employment relationship. One of the directions of the labour law reform should be to improve the quality of the labour law in both its substantive as well as technical-legislative aspects. The planned reform should also exert influence on restructuring and increasing the level of different employees' rights, although the economic situation does not allow to expect too much in that respect. The reform should also strengthen the mechanisms securing the observance of those rights by the management of enterprises.
Basic assumptions of the labour law reform